‘Returning to the faith of our forefathers’: The Role of Historical Consciousness in Shaping Christian Missionary Work in Nineteenth-Century Taiwan - Charouz, Ladislav (Studies in world christianity, 2022)
This essay examines Catholic and Protestant missionary efforts in nineteenth-century Taiwan, emphasising real and perceived historical continuities from missionary work during the seventeenth century, as well as historical consciousness. The first section, entitled ‘Inventing a Restoration’, challenges the commonly accepted assumption implicit in many works, that nineteenth-century missionaries, whether Presbyterian or Catholic, were truly the natural successors to colonial-era missionaries they construed and portrayed themselves to be. Instead, the essay makes the case that the link to the colonial era was in part consciously cultivated and reinforced, serving the purpose of an etiological myth that helped stake a claim to the island’s unconverted masses. The second section, ‘Living in History’, examines the missionaries’ self-reinforced historical consciousness, and the role it played in moulding their own self-perception. Finally, the third section, ‘Memory and Strategy’, argues that the missionaries’ historical consciousness, as well as that of the Taiwanese indigenous population, shaped the strategies used for evangelisation. Indeed, it appears that missionary strategy in fact partly relied on reinforcing a historical consciousness of the colonial era among indigenous Taiwanese. As this essay hopes to demonstrate, there is much more to say about the spiritual legacy of seventeenth-century colonialism in Taiwan than has previously been thought.